2017
DOI: 10.4236/ijmpcero.2017.63029
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Comparison of 4D Computed Tomography (4DCT) and 4D Cone Beam Computed Tomography (4DCBCT)

Abstract: The ability of respiratory-correlated fan beam CT (4DCT) and respiratory-correlated cone beam CT (4DCBCT) to accurately estimate tumor volume is critical to accurate dosimetry and treatment verification for lung stereotactic body radiation therapy (SBRT) and other motion-managed therapies. However, it is known that 4DCT and 4DCBCT differ in aspects of image acquisition and reconstruction that may lead to discrepancies between the two modalities. To evaluate quantitative differences between 4DCT and 4DCBCT imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…Previous studies have also demonstrated that 4D CBCT accurately assesses target volume. 21 It may also be useful to include 4D CBCT imaging in the treatment planning process for conventional fractionation to more accurately determine ITV, where clinics lack 4D CT capabilities but have 4D CBCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also demonstrated that 4D CBCT accurately assesses target volume. 21 It may also be useful to include 4D CBCT imaging in the treatment planning process for conventional fractionation to more accurately determine ITV, where clinics lack 4D CT capabilities but have 4D CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 4D CT has been shown to suffer from motion artifacts leading to 4D CBCT better evaluating target volumes when using a motion phantom with a few different sinusoidal and patient specific motion parameters. 21 Lastly, phantom target motion between the two imaging modalities has been shown to be comparable but with very few different motion parameters explored. 22 These studies, however, have not explored how a wide variety of combinations of amplitude and cycle time for the target motion affect the agreement between 4D CT and 4D CBCT evaluation of target trajectories and where evaluation is hindered due to artifacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For treatment planning, treatment verification, and adaptive radiation in many malignancies, accurate Computed Tomography (CT) studies in the presence of respiratory motion are required [1]. The use of radiotherapy for lung cancer is growing, with Stereotactic Ablative Radiotherapy (SABR) currently being recommended as the first-line therapy for patients with Stage I NSCLC who are medically inoperable and require non-invasive treatment options [2].…”
Section: Introductionmentioning
confidence: 99%
“…ITV is calculated through examination of the Four-Dimensional Computed Tomography (4DCT) images in the case of tumors moving with respiration, such as lung cancer [8]. The radiotherapy plans are typically created using ITV along with setup margins [1,5,8,9]. Comparing the Cone Beam CT (CBCT) acquired prior to treatment with estimated target position and motion to the primary planning CT scan acquired during the simulation is a standard method for doing radiotherapy image-guided verification [10].…”
Section: Introductionmentioning
confidence: 99%